(untitled) (Innovative professional education, 2022)
Blended learning can be understood as a set of tools and methods, which includes a combination of multimedia technologies, streaming video on electronic media, virtual classes, voice and e-mail, conferencing, video streaming and more. Blended learning should be an ideal solution for the rapid acquisition of new information in accordance not only with the needs of society, but also taking into account the needs of the learner. The positive aspects of blended learning are substantiated.